The Influence of Nature on Learning: The Case of Fosen Folk School in Norway (LEARNing Landscapes, 2012)
This institutional ethnography provides an intensive, holistic description and compelling story of a different way of learning. It creates insight and understanding about learning that is not possible in the confines of school systems driven and governed by global economics. How do the instructors, headmaster, and students at Fosen Folk School in Norway teach/learn in a non-academic residential school? Their way of learning helps explain the complex territory between the instincts and tendencies that govern our learning when it is unfettered by institution/government standards, and the norms/values which characterize what is thought, within the formal learning system, to constitute effective teaching/learning. The relationship of self to people, nature, and the environment becomes discernible, understandable.
Keywords: ethnography; learning; informal learning